ArtiaX: An electron tomography toolbox for the interactive handling of sub‐tomograms in UCSF ChimeraX. (16th November 2022) - Ermel, Utz H.; Arghittu, Serena M.; Frangakis, Achilleas S.
Abstract: Cryo‐electron tomography analysis involves the selection of macromolecular complexes to be used for subsequent sub‐tomogram averaging and structure determination. Here, we describe a plugin developed for UCSF ChimeraX that allows for the display, selection, and editing of particles within tomograms. Positions and orientations of selected particles can be manually set, modified and inspected in real time, both on screen and in virtual reality, and exported to various file formats. The plugin allows for the parallel visualization of particles stored in several meta data lists, in the context of any three‐dimensional image that can be opened with UCSF ChimeraX. The particles are rendered in user‐defined colors or using colormaps, such that individual classes or groups of particles, cross‐correlation coefficients, or other types of information can be highlighted to the user. The implemented functions are fast, reliable, and intuitive, exploring the broad range of features in UCSF ChimeraX. They allow for a fluent human–machine interaction, which enables an effective understanding of the sub‐tomogram processing pipeline, even for non‐specialist users.